Traffic Linking of the Baltic and the Central European Countries with the Adriatic - Ivaković, Čedomir; Legac, Ivan; Mavrin, Ivan (Promet - Traffic&Transportation, 2012)
The paper analyses new projects of the European trafficnetwork as well as the extension of conidors defined in 1997 inHelsinki. For connecting of the Baltic and Central Europeancoun/Jies with the Ad1iatic, the projects TEM 1 and 2, ViaBaltica and TINA are of great importance. The programme ofthe TINA project includes road and railway conidors and relieson the 7th Danube conidor. The interrelations between trafficbranches in the EU are presented, with the greatest share ofroad traffic, followed by railway and 1iver traffic. The compOiisonindicates similar relations between single transp01tationbranches in the period from 1979 to 1991 in the Republic ofCroatia.